Menakar Nilai Kemanfaatan Penangguhan Walimat Al-‘Ursy Di Masa Darurat COVID-19 Melalui Analisis Sadd Adz-Dzari’ah - M Nur Kholis Al Amin (Universitas Cokroaminoto Yogyakarta, 2020)
In the study of Islamic marriage law, the law of carrying out walimat al-‘ursy is sunnah muakkad. However, in connection with the Covid-19 Pandemic Virus, it was banned temporally by the government, even through a circular number; P-004/DJ.III/ Hk.007/04/2020, issued by the Ministry of Religion. By literature research known that Prohibition and prevention aimed at gathering people in large groups, both in terms of ibadah and muamalat is an attempt to break the chain of the spread of the COVID-19 virus pandemic. Therefore, further studies on prevention, especially prevention of the implementation of the walimat al-‘ursy during the COVID-19 virus pandemic will be examined through the analysis of sad adz-dzari'ah.